Incidence rates and clinical characteristics of primary gastrointestinal non-Hodgkin lymphoma: a population study. Issue 5 (May 2020) - Dizengof, Vitaly; Levi, Itai; Etzion, Ohad; Fich, Alexander; Blum, Avital; Chertok, Ilana R. Azulay; Ben-Yakov, Gil; Rouvio, Ory; Greenbaum, Uri
Abstract : Background & Aims: After the rise of lymphoma incidence in the 1990's, there is a paucity of epidemiologic studies describing the characteristics of primary gastrointestinal non-Hodgkin's lymphoma (PGIL). This epidemiologic survey aims to identify recent trends in PGIL. Methods: A retrospective, population-based study describing adult patients with PGIL in the Israeli Negev region between 1998 and 2013. Results: 131 patients were diagnosed with PGIL, representing an annual incidence rate of 22.42/100, 000, compared to 35.87/100, 000 in the overall Israeli population. Both incidence rates did not significantly change during the study period. The median age was 66 years, and the most common presentation was in the stomach (49.6%) and oral cavity (18.3%). Histologically, diffuse large B cell lymphoma (DLBCL) was predominant (55.0%). Most patients (66.4%) had early stage disease. Only T-cell lymphoma showed a male predominance (14.7% versus 5.4%, P =0.008). Fifty patients (44.2%) had H. pylori testing, and 35 (70.0%) were positive. Of these, 91.4% received eradication treatment, and 57.1% were negative thereafter. Most patients received CHOP or RCHOP protocols (16.0% and 48.1%, respectively). Complete response was achieved in 53.4%. Median follow-up was 48 months, and 62 patients (47.3%) died during the study period. Liver involvement had a worse prognosis, (33.0% 5-year survival) compared to upper and lower GI disease(70.5% and 46.8% respectively, P =0.003 for the comparison between liver and other locations). T-cell lymphoma had worse survival (11 months vs. not reached, P =0.003). Conclusions: This study demonstrates the incidence, and clinical characteristics of PGIL in the Negev region. It is important to identify disease characteristics, thus facilitating better disease detection and prognostication.